2006
DOI: 10.1111/j.1467-7687.2006.00505.x
|View full text |Cite
|
Sign up to set email alerts
|

Human behaviour and development under high‐altitude conditions

Abstract: Although we are far from a universally accepted pattern of impaired function at altitude, there is evidence indicating motor, perceptual, memory and behavioural deficits in adults. Even relatively low altitudes (2500 m) may delay reaction time, and impair motor function. Extreme altitude exposure (>5000 m) may result in more pronounced impairment that can persist after returning to the lowlands. Research into the effects of altitude exposure earlier in development is lacking by comparison. Un-acclimatized chil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
49
1
4

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(55 citation statements)
references
References 94 publications
1
49
1
4
Order By: Relevance
“…For the behavior result, the high altitude group reacted slower than the low altitude group under all conditions. Consistent with other studies, the reaction time delay in the high altitude group might reflect altered sensoriperceptual processing 7,43,44 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…For the behavior result, the high altitude group reacted slower than the low altitude group under all conditions. Consistent with other studies, the reaction time delay in the high altitude group might reflect altered sensoriperceptual processing 7,43,44 .…”
Section: Discussionmentioning
confidence: 99%
“…Sustained exposure to high altitude leads to cognitive decrement, such as impairment in attention, memory, judgment, and emotion 4 . Research has demonstrated that cognitive impairment due to altitude starts at 2,500 m above sea level [5][6][7] , because brain vulnerability to hypoxia increases beginning at 2,500 m 8 . Spatial attention may be particularly affected by high altitude exposure.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Neurophysiological functions such as event-related potentials, reaction time, psychomotor performances or cognitive processes have been reported to be aVected under exposure to high altitude (Virues-Ortega et al 2004;Virues-Ortega et al 2006). For example, Li et al (2000) investigated psychomotor performance and visual reaction time after acute exposure to hypoxia of 1 h duration at altitudes of 300 m (control), 2,800, 3,600, and 4,400 m. The results showed no diVerences in performance at 2,800 m, but tremor decreased signiWcantly at 3,600 and 4,400 m. Consequently, the literature suggests that the critical altitude for changes in higher cognitive functioning appears to lie between 4,000 and 5,000 m. It has been shown that there is little variation at 3,800 m, but a marked deterioration in cognitive ability occurs at 5,000 m (Nelson 1982).…”
mentioning
confidence: 99%
“…having the ability to receive through the senses diverse images, impressions or external sensations, or to understand and to know something (Pinel). It is commonly believed that attention and perception are hardest to reach in communities that reside at high altitudes above the sea level, since living in high altitudes exposes our body to lower oxygen pressure (Virués-Ortega et al, 2006).…”
Section: Discussionmentioning
confidence: 99%